The stonefly Taeniopteryx schoenemundi (Mertens, 1923) (Insecta: Plecoptera) conquers Europe’s busiest waterway the Lower River Rhine - Lorenz, Armin W.; Enss, Julian; Hörren, Thomas P. B.; Enting, Klaus (Zootaxa, 2025)
Recent observations of winter-active Taeniopterygidae in mid-sized Central European rivers reveal that these large-river stonefly species, previously thought to have been extirpated by severe water pollution, have persisted in hidden refugia. During February and March 2024, we conducted a comprehensive survey along a 300-km section of the lower River Rhine in North Rhine-Westphalia, Germany, spanning from Bonn to the Dutch border. We recorded adults and exuviae of the stonefly Taeniopteryx schoenemundi (Mertens, 1923) at 13 locations along the Rhine and 2 additional sites in its tributaries, the Ruhr and Wupper rivers. These findings, together with recent records from other Rhine tributaries, suggest that colonization by T. schoenemundi has occurred from these tributary populations. Significant anthropogenic alterations in the river’s habitat may have created conditions now favorable for T. schoenemundi, a species not historically observed in the Rhine. This discovery marks the first confirmed presence of a stonefly in the lower Rhine in nearly a century, representing a noteworthy milestone in the river’s recovery. Furthermore, the resurgence of T. schoenemundi within this heavily modified waterway underscores the potential for substantial improvement in water quality, offering renewed prospects for the restoration of native biodiversity in the Rhine system.